1994
DOI: 10.1136/jmg.31.12.978
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Yqh translocations.

Abstract: Two initially presumed Yqh translocations, one to Xp and another to 21p, were assessed by conventional banding procedures, 5-azacytidine treatment, electron microscopy, and fluorescence in situ hybridisation. While the Yqh nature of the heterochromatic block from Xp was confirmed, this was not the case with the 21ph + variant. In conclusion, conventional banding techniques are insufficient to diagnose Y;G translocations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Follow-up at 7 months showed normal growth and development. We have shown that conventional cytogenetics and molecular cytogenetics are complimentary techniques in diagnosis of rare chromosomal rearrangement involving chromosome Y [17]. While conventional CBG banding demonstrated that the extra material translocated onto the acrocentric chromosome was heterochromatic in nature, molecular techniques identified the chromosome Y origin of the heterochromatic material.…”
Section: Discussionmentioning
confidence: 97%
“…Follow-up at 7 months showed normal growth and development. We have shown that conventional cytogenetics and molecular cytogenetics are complimentary techniques in diagnosis of rare chromosomal rearrangement involving chromosome Y [17]. While conventional CBG banding demonstrated that the extra material translocated onto the acrocentric chromosome was heterochromatic in nature, molecular techniques identified the chromosome Y origin of the heterochromatic material.…”
Section: Discussionmentioning
confidence: 97%
“…In the case of autosomes, the short arms of the acrocentric chromosomes, mainly of chromosome 15, are most frequently involved in the rearrangement, whereas the distal short arm of the X chromosome is the most common acceptor site in sex chromosomes [Fernández et al, 1994]. Hsu [1994] reviewed the results of 50 cases of postnatal Y;A translocations.…”
Section: Discussionmentioning
confidence: 99%